Rani Manicka's Touching Earth: a true polyphonic novel - Barani, Forough; Wan Yahya, Wan Roselezam (SAGE Publications, 2013)
Rani Manicka’s Touching Earth demonstrates a narrative discursive style which is indeed an appropriate ground for the study of multiple voices and worldviews. Manicka’s representation of the world through an utmost plurality of consciousnesses, each playing its part on an equal dialogical basis to demonstrate the truth, parallels what Russian theorist Mikhail Bakhtin (1895-1975) describes as a “Polyphonic Novel.” The main aim of this study is to discover, in Rani Manicka’s Touching Earth, the polyphonic elements that Bakhtin attributed to Dostoevsky’s novels. This article further seeks to identify the dialogic relationship between the characters, the active participation of the reader, and the author’s position with regard to these. The final goal of this study is to establish the quality of unfinalizability, the capacity to outgrow the determined fixed definitions, and the shared perception of truth in this novel. As there have been limited Bakhtinian studies on Asian texts and, in particular, none on Rani Manicka’s novels, this study attempts to fill this gap in the literature and thus contribute to the body of research on the dialogical dimension of the novel.